2018
DOI: 10.1111/tme.12551
|View full text |Cite
|
Sign up to set email alerts
|

Sero‐prevalence and viremia status of dengue virus among asymptomatic blood donors post epidemic outbreak in Chinese Guangzhou in 2015

Abstract: Dear Sir,Dengue virus (DENV) has been listed on a catalogue from the American Association of Blood Banks (AABB) as transfusion transmissible infectious (TTIs) (Stramer et al., 2009). Routine screening for DENV RNA with nucleic acid testing (NAT) on donors' samples has been suggested to reduce the transfusion-transmitted risk of DENV in several countries and regions with high epidemic, such as Honduras (Linnen et al., 2008) and Brazil (Dias et al., 2012).In China, the third historically largest dengue hemorrhag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The upper limit of the 95% CI demonstrated a maximum prevalence of DENV RNA of 0.63% (CI: 95%) if we had tested all donated blood for DENV RNA. Similarly, studies from other geographic locations demonstrated a prevalence of DENV RNA between 0.0 (China, Australia) [ 20 – 22 ] and 0.07% (Puerto Rico) [ 23 ]. In all cases, the detected prevalence of DENV RNA was lower than those of studies performed in Brazil [ 3 ] and Saudi Arabia (5.5%) [ 24 ].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The upper limit of the 95% CI demonstrated a maximum prevalence of DENV RNA of 0.63% (CI: 95%) if we had tested all donated blood for DENV RNA. Similarly, studies from other geographic locations demonstrated a prevalence of DENV RNA between 0.0 (China, Australia) [ 20 – 22 ] and 0.07% (Puerto Rico) [ 23 ]. In all cases, the detected prevalence of DENV RNA was lower than those of studies performed in Brazil [ 3 ] and Saudi Arabia (5.5%) [ 24 ].…”
Section: Discussionmentioning
confidence: 97%
“…During the next outbreak (2015), the prevalence of anti-DENV IgM declined to 0.4%. This decrease may have been a result of actions of the Chinese Center for Disease Control (CDC), which improved control and prevention strategies for DENV [ 20 ], but may also have been a result of lower circulation of DENV (non-epidemic year) or circulation of a different serotype. In contrast, a much lower seroprevalence was detected in Singapore (2.83%) and Australia (0.22%), regions in which DENV is endemic; however, they represent developed countries with a possible implementation of control measures to curb DENV outbreaks.…”
Section: Discussionmentioning
confidence: 99%
“…65 Most of the investigations in the reviewed articles showed a high seroprevalence of dengue viral markers (IgM/IgG) among potential blood donors who were asymptomatic. [66][67][68][69][70][71][72][73][74] Therefore, it is essential to practice meticulous preventive techniques to ensure the safety of blood transfusions and to prevent the spread of the DENV in an endemic area. 75…”
Section: Global Distributions Of Research Work Around the Dengue Viru...mentioning
confidence: 99%